Percutaneous Correction Surgery of Hammer Toes with Biodegradable Pins - Pablo Sotelano MD; Daniel S. Villena MD; Ana C. Parise MD; Leonardo A. Conti MBA, PhD; Nelly M. Carrasco MD; Jonathan M. Verbner MD; Maria Gala Santini Araujo MD (Foot & Ankle Orthopaedics, 2022)
Category: Lesser Toes; Midfoot/Forefoot Introduction/Purpose: The standard treatment for deformities in lesser toes is proximal interphalangeal arthrodesis with Kirschner wires. It is relatively inexpensive but complications have been described such as infection, recurrences and misalignment. New devices were developed, among them biodegradable pins avoid the need for withdrawal and exposure to the outside. The objective of this study was to describe the clinical and radiological results one year after surgery in a group of patients with a diagnosis of rigid hammer toes, who underwent percutaneous surgical correction with a biodegradable pin. Methods: Methods: We present a retrospective study in a consecutive series of cases with a diagnosis of hammer toe operated between January 2016 and December 2018. Patients older than 18 years of age who underwent a percutaneous proximal interphalangeal arthrodesis, with a biodegradable pin, were included. The patients were asked through a survey to rate the results obtained with the intervention (excellent, very good, good, fair and bad). loss of contact with the ground was evaluated with podobarography. The patients were evaluated with weightbearing X rays to assess interphalangeal alignment and consolidation. We used the AOFAS scale to assess clinical results, preoperatively and one year after surgery. Postoperative complications, infection, wound dehiscence, rupture of osteosynthesis material, loss of correction were also evaluated. Results: 117 patients were identified, 23 (16%) underwent bilateral surgery (140 feet), with a total of 220 lesser toes who underwent proximal interphalangeal arthrodesis stabilized with percutaneously biodegradable pin. 50% had a minimum follow-up of 1 year. The pre-surgical AOFAS of 52 improved to 95 points in the postoperative period. In 96 (43.63%) fingers, an F1 base osteotomy was performed to correct the alignment in the coronal plane. We observed pseudo osteoarthritis in 5% of the toes but with good alignment. We observed 6% of floating fingers, the pin was removed in 5 fingers; without loss of correction. In 1.36% cases it migrated early, causing a recurrence of the lesion. Patient satisfaction was excellent or very good in 79 %. Conclusion: According to our serie results, we consider that percutaneous technique with biodegradable pins manages to maintain adequate alignment and a consolidation rate both in radiological and clinical results with good patient satisfaction. No infection case was reported. We found a low rate of biodegradable pin removal. For its part, the biodegradable plug allows osteotomies to be performed with the implant already in place, it does not require routine removal of the implant, reducing the need for a second intervention.